Penggunaan Protein Bahan Makanan berdasarkan Keatahanan Degradasinya pada Domba - Nur Aeni Sigit (Buletin Ilmu Makanan Ternak, 1987)
The Previous in Vitro experiment indicated clearly that urea (A), peanut leaves (B), cassava leaves (C), soybean meal by product (D) and coconut oil meal (D) resulted a significant different levels of ammonia, Differences in rumen ammonia concentrations could eventually be used as an in vivo index of protein degradation value in the rumen and thus predict the amount of "by pass protein" from a protein meal.A randomized block feeding experiment was conducted to examine some nutritional aspects of five nitrogen sources using 15 local lambs.The results showed that quality of peanut leaves were good enough as protein sources for ruminant . The protein efficiency of plant feeds used in this experiment were significantly better than urea.